Pola Interaksi Guru dan Siswa Tunanetra - Widyastuti, Rany (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to describe the pattern of interaction between teachers and students and between students with other students on learning VII grade SMPLB A Bina Insani Bandar Lampung. This research is a qualitative research. The subject of this research is one teacher and all students of class VII SMPLB A Bina Insani Bandar Lampung, amounting to 5 people where 1 student is light blind (low vision) and 4 students total blind. The technique of validity of data used is by triangulation time, that is by seeing the data of an interaction between a teacher with the student and between student on two observations done on a different day. The results of this study indicate that the pattern of interaction of teachers and students with visual impairment in learning VII grade SMPLB A Bina Insani Bandar Lampung is a two-way interaction but without the interaction between students with one student, either in the category of information (BIn) (UIn), as well as delay information (TIn).